Why and When Transformational Leadership Influences Followers Qualitative Job Insecurity: A Three-Wave Moderated Mediation Study - Lopez-Bohle, S; Muñoz-Medina, L (John Wiley and Sons Inc, 2024)
This study explored the mediation role of follower organization-based self-esteem (OBSE) and the moderation role of workplace friendship in the relationship between transformational leadership and follower qualitative job insecurity. We adopted a three-wave longitudinal design and collected survey data from 142 Chilean employees. Cross-lagged mediation panel analysis indicated that transformational leadership had a lagged effect on follower OBSE, which, in turn, had a lagged effect on follower qualitative job insecurity. Further, follower workplace friendship moderated the effect of transformational leadership on follower OBSE such that transformational leadership only promoted follower OBSE when followers had high workplace friendship but did not significantly moderate the indirect effect of transformational leadership on follower qualitative job insecurity via OBSE. Integrating the leadership literature with the job insecurity literature, our study takes the first attempt to explore how, why, and when transformational leadership may influence follower qualitative job insecurity. © 2024 International Association of Applied Psychology.